Rational optimist : how prosperity evolves - Ridley, Matt. (London : Fourth Estate, 2010)
The "New York Times"-bestselling author of "Genome" and "The Red Queen" offers a provocative case for an economics of hope, arguing that the benefits of commerce, technology, innovation, and change--cultural evolution--will inevitably increase human prosperity.
Includes bibliographical references and index.
Keywords: Wealth; Practical reason; Optimism